Teknik Pembenihan Nila Salin (Oreochromis niloticus) Secara Alami di UPTD Balai Perikanan Air Laut Dan Payau Teluk Buo Sumatera Barat - Panjaitan, Yuni Sara; Rolin, Febrina (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2026)
Saline tilapia (Oreochromis niloticus) culture is a strategic option for utilizing brackish coastal waters. This study aimed to evaluate natural hatchery techniques, identify success factors, and provide recommendations to improve productivity. Conducted from July to September 2025 at the Marine and Brackish Water Fisheries Center, Teluk Buo (Padang), the study used direct and participatory observation. Data included fecundity, feed consumption, fry survival, and water quality. Spawning was carried out naturally with a 1:3 male-to-female ratio at 17–18 ppt salinity. Results showed high fecundity (3,500 eggs per female) and fry survival rate of 83%. Daily feed consumption was 1.2 kg for 80 broodstock. Water quality remained optimal (pH 7, temperature 28–30°C, salinity 17–18 ppt, DO >5 mg/L). Hatchery success was influenced by broodstock quality, high-protein feed, water management, and biosecurity. These findings can support the development of saline tilapia hatchery in coastal Indonesia.